2019
DOI: 10.1177/1028315319861353
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-Being of Angolan Students in Portugal

Abstract: This study examined the subjective well-being (SWB) of international students. International students represent one of the biggest and most relevant sojourners groups. The sample included 204 Angolan international students who attended Portuguese universities and a control group of native-born Portuguese students. Using quantitative survey research methods, the relative strengths of demographic, acculturation, and sociocultural adaptation factors in predicting two indicators of SWB (overall well-being and acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 64 publications
(75 reference statements)
0
9
0
1
Order By: Relevance
“…However, satisfaction offers a particular view on the complex experiences of both domestic and international students. Future research could focus on education outcomes such as grades or academic performance (Gang et al, 2009), or broader measures of well-being (Baik et al, 2019;Neto, 2019), going beyond satisfaction to include engagement, friendships, relationships, social life, and experiences of discrimination (Brown & Jones, 2013). Regarding maternal education, and its endurance on satisfaction in this study after adding region of origin and cultural distance, it is important to note broader evidence of strong links between maternal education and the outcomes of their children (Currie & Moretti, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, satisfaction offers a particular view on the complex experiences of both domestic and international students. Future research could focus on education outcomes such as grades or academic performance (Gang et al, 2009), or broader measures of well-being (Baik et al, 2019;Neto, 2019), going beyond satisfaction to include engagement, friendships, relationships, social life, and experiences of discrimination (Brown & Jones, 2013). Regarding maternal education, and its endurance on satisfaction in this study after adding region of origin and cultural distance, it is important to note broader evidence of strong links between maternal education and the outcomes of their children (Currie & Moretti, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The concept was first operationalized in seminal work by Vallerand and Bissonnette (1990), with Diener (1995) further developing understandings related to well-being and cross-cultural differences. Neto (2019) has identified that sociocultural adaptation factors predict satisfaction, with satisfaction proving to have particular utility in the study of cultural variation. To date, broad patterns on the experiences of international students according to global region of origin remain underexamined.…”
Section: International Students' Adjustment Experiences and Satisfaction In Their Host Countriesmentioning
confidence: 99%
See 3 more Smart Citations